Should states in the USA value species at the edge of their geographic range?. Issue 6 (22nd May 2015) - Steen, David A.; Barrett, Kyle
ABSTRACT Given limited resources and current mechanisms for conservation of rare and imperiled species, a common practice is to prioritize species that are in need of conservation attention. Agencies and individuals responsible for the conservation of species within given boundaries may deprioritize the conservation of species that are rare within those boundaries if the species' range is extensive (e.g., such as when populations occur at the edges of a species' geographic range). We overlapped amphibian and reptile geographic ranges with state boundaries in the United States to show that many of the species within any given state could be considered peripheral and are therefore vulnerable to conservation inaction based on that fact alone. We argue that a species' overall geographic range should not be used as a primary reason for deprioritizing the conservation of a species within a given boundary, and illustrate that even populations at the edges of a species' range have value to the overall conservation of that species and are integral parts of ecological communities wherever they occur. We urge decision makers and biologists to consider these arguments during ranking processes, and not reflexively deprioritize the conservation of species at the edges of their geographic ranges. © 2015 The Wildlife Society.